Countering ISIS's Social Media Influence. Issue 1 (2nd January 2016) - Lieber, Paul S.; Reiley, Peter J.
Abstract : The success of the Islamic State in Iraq and Syria (ISIS) in recruiting and sustaining foreign fighter flow (Baron, 2016) is seen by many as a product of the organization's potent social media efforts (Al-Tamimi, 2014; Brooking & Singer, 2016). This research argues, however, that a different approach to both problem analysis (Metz, 2015) and measures of effectiveness can potentially counter ISIS's influence efforts. This includes adopting a whole-of-government approach to synchronize efforts and voice (Office of the Spokesperson, U.S. Department of State, 2016; National Defense Authorization Act, 2016).